2014
DOI: 10.1159/000368120
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Monitoring of the Serotonin Transporter Gene Expression to Assess Major Depressive Episode Evolution

Abstract: Background: Mood disorders are frequently characterized by uncertain prognosis and studying mRNA expression variations in blood cells represents a promising avenue of identifying biomarkers for mood disorders. State-dependent gene expression variations have been described during a major depressive episode (MDE), in particular for SLC6A4 mRNA, but how this transcript varies in relation to MDE evolution remains unclear. In this study, we prospectively assessed time trends of SCL6A4 mRNA expression in responder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The serotonin transporter (SLC6A4) is the main target of numerous antidepressants and has been identified as a potential candidate biomarker involved in antidepressant response, although genetic studies have found conflicting results (Gadad et al, 2017). Numerous studies based on relatively small cohorts described variation of the serotonin transporter gene peripheral expression according to depressive symptoms of patients compared to psychiatrically healthy controls (Belzeaux et al, 2010;Belzeaux et al, 2014b;Iga et al, 2005;Lima et al, 2005;Tsao et al, 2006). Previous studies demonstrated that SLC6A4 mRNA could vary according to the emergence and the treatment of MDE (Belzeaux et al, 2014a).…”
Section: How: Statistical Tools and Other Methodological Challengesmentioning
confidence: 99%
“…The serotonin transporter (SLC6A4) is the main target of numerous antidepressants and has been identified as a potential candidate biomarker involved in antidepressant response, although genetic studies have found conflicting results (Gadad et al, 2017). Numerous studies based on relatively small cohorts described variation of the serotonin transporter gene peripheral expression according to depressive symptoms of patients compared to psychiatrically healthy controls (Belzeaux et al, 2010;Belzeaux et al, 2014b;Iga et al, 2005;Lima et al, 2005;Tsao et al, 2006). Previous studies demonstrated that SLC6A4 mRNA could vary according to the emergence and the treatment of MDE (Belzeaux et al, 2014a).…”
Section: How: Statistical Tools and Other Methodological Challengesmentioning
confidence: 99%
“…The serotonin transporter protein (SLC6A4) is the main target of many antidepressants, although the relationship between pathophysiology and therapeutic effects of antidepressants is still not clear 107,108 . Based on previous studies on SLC6A4 mRNA gene expression variation in peripheral tissues, Belzeaux et al 109 explored whether SLC6A4 mRNA could be a target biomarker of antidepressant treatment during a major depressive episode that varies between the baseline and the 30-week followup period in responder patients. Interestingly, decreased expression levels of SLC6A4 were observed in responder patients across a 30-week follow-up, whereas nonresponder subjects showed increased mRNA levels of SLC6A4.…”
Section: Treatmentmentioning
confidence: 99%
“…SLC6A4 expression (mRNA level) in peripheral cells (lymphocytes) was also investigated, since lymphocytes are thought to potentially act as a neural probe for studying psychiatric dis-orders (Gladkevich et al 2004). Studies on small samples of depressed patients suggested a reduction of SERT expression after antidepressant treatment (Iga et al 2005;Tsao et al 2006) with a possible positive correlation with response (Belzeaux et al 2014), but opposite findings also exist (Pena et al 2005;Belzeaux et al 2010). The reduction of SERT expression in the rat brain was associated with antidepressant-like behaviours (Thakker et al 2005) and key markers of antidepressant action: reduced expression and function of 5-HT1A-autoreceptors, elevated extracellular 5-HT in the forebrain and increased neurogenesis and expression of plasticity-related genes (BDNF, VEGF, ARC)in the hippocampus (Ferres-Coy et al 2013).…”
Section: Peripheral Biomarkersmentioning
confidence: 99%